Prevalence of subclinical bactibilia in apparently healthy shelter dogs. (15th July 2021) - Verwey, E.; Gal, A.; Kettner, F.; Botha, W. J.; Pazzi, P.
Abstract : Objectives: To determine the prevalence of subclinical bactibilia in apparently healthy shelter dogs and characterise serum liver enzymes activities, hepatobiliary histopathology and bile cytology in apparently healthy dogs with and without bactibilia. Materials and Methods: Healthy, abandoned dogs euthanased for non‐medical reasons were prospectively recruited for this cross‐sectional study. Whole blood, collected immediately before euthanasia, was submitted for serum liver enzyme activity (alkaline phosphatase, alanine aminotransferase and gamma‐glutamyl transferase) analyses. Bile, gall bladder and liver samples were collected aseptically from dogs within 25 minutes of euthanasia. Bile was submitted for bacterial culture and cytology in all dogs. Gall bladder and liver samples were submitted for histopathological examination in bactibilic dogs and nine randomly selected non‐bactibilic dogs. Results: Sixty‐five healthy dogs were included in this study. Bactibilia was diagnosed in 10.8% (7/65) of dogs, with 9.2% (6/65) of dogs diagnosed on cytological examination and 4.6% (3/65) on culture. Elevated alanine aminotransferase activities were present in one bactibilic and five non‐bactibilic dogs; and elevated gamma‐glutamyl transferase activities in one bactibilic and two non‐bactibilic dogs. No dogs had elevated alkaline phosphatase activities. Histopathological changes in bactibilic and non‐bactibilic dogs included lymphoplasmocellular cholecystitis (7/7 and 9/9), gall bladder oedema (7/7 and 9/9), hepatic vacuolar degeneration (6/7 and 8/9), cholangitis (5/7 and 7/9), hepatic nodular hyperplasia (3/7 and 5/9) and hepatic cholestasis (2/7 and 4/9). Clinical Significance: This study confirms that subclinical bactibilia occurs in a small number of apparently healthy shelter dogs and that subclinical hepatobiliary histopathological abnormalities can occur in apparently healthy bactibilic and non‐bactibilic dogs.